Slowing gait speed precedes cognitive decline by several years. Issue 9 (9th February 2022) - Skillbäck, Tobias; Blennow, Kaj; Zetterberg, Henrik; Skoog, Johan; Rydén, Lina; Wetterberg, Hanna; Guo, Xinxin; Sacuiu, Simona; Mielke, Michelle M.; Zettergren, Anna; Skoog, Ingmar; Kern, Silke
Abstract: Introduction: In this longitudinal study, we aimed to examine if slowing gait speed preceded cognitive decline and correlated with brain amyloidosis. Methods: The sample (n = 287) was derived from the Gothenburg H70 Birth Cohort Studies, with follow‐ups between 2000 and 2015. Gait speed was measured by indoor walk, and cognition using the Clinical Dementia Rating (CDR) score. All participants had CDR = 0 at baseline. Some participants had data on cerebrospinal fluid (CSF) amyloid beta (Aβ)1‐42 concentrations at the 2009 examination. Results: Gait speed for participants who worsened in CDR score during follow‐up was slower at most examinations. Baseline gait speed could significantly predict CDR change from baseline to follow‐up. Subjects with pathological CSF Aβ1‐ 42 concentrations at the 2009 visit had lost more gait speed compared to previous examinations. Discussion: Our results indicate that gait speed decline precedes cognitive decline, is linked to Alzheimer's pathology, and might be used for early detection of increased risk for dementia development.